Simulating advanced focused ion beam nanomachining: a quantitative comparison of simulation and experimental results. (5th October 2018) - Mahady, Kyle T; Tan, Shida; Greenzweig, Yuval; Raveh, Amir; Rack, Philip D
Abstract: A simulation study of focused ion beam (FIB) sputtering in SiO2 is presented. The basis of this study is an enhanced version of the EnvizION Monte Carlo simulation program for FIB processing, which previously was restricted to targets composed of a single atom. A Monte Carlo method is presented for the simulation of FIB sputtering in SiO2 in three-dimensions, with ion implantation, to elucidate the complex dynamics of nanoscale milling of compound targets. This method is applied to the simulation of sputtering experiments using both Ne + and Ga + ion beams. We compare simulations using experimentally derived 'measured' beam profiles for each ion species, and 'effective' beam profiles which are chosen to reproduce experimental results. Simulations using the 'measured' beam profiles produce vias which are narrower than experiments, while the 'effective' beam profiles for both Ne + and Ga + are significantly wider than the 'measured' profiles. The difference between the 'measured' and 'effective' beam profiles is attributed to widening of the milling effects of the beam beyond its static dimensions, due to platform level artifacts such as vibrations and, possibly, charging. Simulations using the 'effective' beam profiles are found to accurately reproduce the depths and overall shape of experimental FIB sputtered vias in test cases, which vary in ion species, beam energy, total dose, and raster parameters. This comparison is the most extensive validation of the EnvizION simulation against experiments to date. However, the location of implanted ions in simulations is shallower than experiments, which is attributed to the fact that implanted species are required to find nearest neighbor vacancies and not allowed to occupy interstitial positions.